From Institutions to Families: Assessing the Progress of Egypt’s National Strategy for Alternative Child Care Reform - El Hagry, Yasmine M (AUC Knowledge Fountain, 2026)
This study serves as a critical mid-term review of the Egyptian National Strategy for Alternative Care for Children and Youth without Parental Care (NACS) (2021-2030). The 10-year strategy overall goal is to shift from institutional care, such as orphanages, to family-based care, such as kafala, the Islamic alternative to legal adoption, for children deprived of parental care. While the global literature strongly advocates deinstitutionalization, empirical research on the operational risks and unintended harms that can arise during such complex transformations remains scarce. Adapting the International Civil Service Effectiveness (InCiSE) Framework, this research uses a qualitative approach to diagnose the implementation reality of the strategy over its first five years. The analysis reveals a significant achievement: the strategy has successfully mainstreamed the kafala system. Additionally, it has elevated aftercare for youth aging out of the system from a neglected blind spot to a high-priority policy agenda, securing unprecedented recognition for these care leavers. However, the findings warn that these strategic wins are undermined by weak legislation and unclear direction, stemming from the delayed enactment of the standalone Alternative Care Law, high administrative turnover, and a workforce specialization gap that relies on generalists rather than specialists. This misalignment increases the risk of unintended harm by prioritizing the closure of institutions over ensuring stable child placements. The research suggests a practical roadmap for the next five years (2026–2030), recommending a shift away from administrative speed toward a child-centered approach, with stronger laws, clearer state funding, and a specialized vocational shift within the social service workforce.